PENGARUH PROFITABILITAS, PERPUTARAN ASET TETAP, DAN RASIO PEMBAYARAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Jessica Febrianti; Santoso Chandra (E-Jurnal Akuntansi TSM, 2022)
The value of the company is very important for a company, investors will be interested in investing if the value of the company is stable and increasing, therefore it is very important for a company to keep the value of the company stable under various conditions, so it is important to examine what factors can influence of firm value. The purpose of this study to determine the effect of profitability, capital structure, managerial ownership, company age, fixed assets turnover, sales growth, shareholder’s equity, and dividend payout ratio. The object of this study is non-financial companies listed on Indonesia Stock Exchange (IDX) from the period of 2018 to 2020. This study used 51 samples with the method used is purposive sampling. Data were analyzed using multiple regression method using SPSS 25. Based on the results of this study shows that profitability, capital structure, and fixed assets turnover have influence toward firm value, while managerial ownership, company age, sales growth, shareholder’s equity, and dividend payout ratio have no influence toward firm value